Nobles and Books: Caramuel’s Architectura Civil Recta y Oblicua in a Valencian Library - Gil Saura, Yolanda (Abaton. Revista de figuración, representación e imágenes de la arquitectura, 2023)
The article analyses the books found at the death of Gaspar de Cervellón in Valencia in 1686. Caramuel’s book on architecture is found alongside other books in which science enters the realm of the jocular and the literary games of the opposition of opposites.